Quercetin: A Potential Candidate for the Treatment of Arthritis - Goyal, Ahsas; Agrawal, Neetu (Current Molecular Medicine, 2022)
Diet plays a significant role in ensuring healthy life, and the bioactive compounds present in food and medicinal plants may be developed as drugs that combat various illnesses. A bioactive flavanoid, quercetin which is a dietary component, possesses numerous health-promoting effects. In preclinical models of rheumatoid arthritis, gouty arthritis and osteoarthritis, quercetin has shown significant joint protective effects. Taking into account the significance of this compound, the present review discusses its anti-arthritic properties, demonstrating its mechanism of action for the treatment of arthritis with its therapeutic potential.
Keywords: phytochemical